Binary organocatalytic system for ring-opening polymerization of ε-caprolactone and δ-valerolactone: Synergetic effects for enhanced selectivity. (February 2019) - Li, Yunxin; Zhao, Na; Wei, Chuanzhi; Sun, Abin; Liu, Shaofeng; Li, Zhibo
Graphical abstract: The binary organocatalytic system comprised ofCTPB and ureas is developed and shows both of high activity and selectivity for the ROP of cyclic esters. Highlights: A simple and synergetic binary catalytic system containingCTPB and urea has been developed. The ROP of ε -CL and δ -VL was highly controlled. The linear and three-arm star block copolymers were readily prepared. The synergetic bifunctional mechanism was investigated. Abstract: Phosphazenes have attracted considerable attention in the field of ring-opening polymerization (ROP) of cyclic esters. However, the application of phosphazenes as catalyst is subject to a trade-off between activity and selectivity (chain propagation versus transesterification/back-biting reaction, e.g., controlled polymerization). Despite extensive research efforts, the development of a new catalytic system having concurrent high activity and selectivity remains a great challenge. In this work, we report that the binary organocatalytic system comprised of cyclic trimeric phosphazene base (CTPB ) and ureas shows both of high activity and selectivity for the ROP of ε -caprolactone ( ε -CL) and δ -valerolactone ( δ -VL) in the presence of alcohol as initiator. It is found that the introduction of ureas would significantly increase the catalytic selectivity during ROP without sacrificing the catalytic activity ofCTPB . Moreover, the polymerizations catalyzed by the title catalytic system exhibit immortal characteristics and thus thousands equivalent of monomer could be converted to polymer efficiently with desired MWs and microstructures. Linear diblock copolymer AB and star copolymers (AB)3 with three identical diblock arms could be readily synthesized by sequential copolymerization using different alcohols as initiators.